Transformation of the state? Reactions to the privatization of security in Great Britain - Jutta Joachim (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
Private Military and Security Companies (PMSCs) have increasingly received attention from International Relations scholars. While most of the research has thus far been conducted with the aim to define the actor, assess the consequences of the services they perform for states' monopoly over the use of force, or to evaluate the options for regulation, societal responses to these companies have been largely ignored. Focusing on Great Britain and the consultative processes that have been initiated by the Foreign and Commonwealth Office with different stakeholders on the options for regulating PMSCs since 2001, this paper constitutes a first step in filling this void in the literature. The analysis of the positions of non-governmental organizations, parlamentarians, the government, and PMSCs is insightful in two respects: First, it sheds light on why the British government has thus far refrained from adopting authoritative controls for PMSCs despite the widely shared assumption that some form of regulation is needed. Second, the findings suggest that a transformation of the state is underway at the intersubjective level. PMSCs and privatization processes in the realm of security are increasingly seen as normal and their legitimacy is no longer questioned.
Keywords: 330; Sicherheitsgewerbe; Privatisierung; Großbritannien